2005
DOI: 10.1080/00365520410009456
|View full text |Cite
|
Sign up to set email alerts
|

Role ofp53codon 72 polymorphism in the risk of development of distal gastric cancer

Abstract: The results of this study suggest that the carriage of the Arg/Arg genotype could be associated with the development of distal GC in this Mexican population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 17 publications
0
21
0
4
Order By: Relevance
“…These results are consistent with our, larger, study. By contrast, two studies reported that the Arg/Arg genotype was associated with an increased risk of gastric cancer [16,22], while other studies found no association [20,[23][24][25][26][27]. Although the reason for these inconsistencies is unclear, they may be explained by differences in ethnicity, small numbers of patients, and substantial interindividual variation in the susceptibility to genetic events and tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with our, larger, study. By contrast, two studies reported that the Arg/Arg genotype was associated with an increased risk of gastric cancer [16,22], while other studies found no association [20,[23][24][25][26][27]. Although the reason for these inconsistencies is unclear, they may be explained by differences in ethnicity, small numbers of patients, and substantial interindividual variation in the susceptibility to genetic events and tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…There are two histologically distinct GC: the diffuse-type and intestinal-type. When GC was not classified by tissue type, the Arg/Arg genotype of p53 codon 72 was found to be related to the development of distal GC in the Mexican population (Pérez-Pérez et al, 2005) and the Arg allele with non-cardias GC in the Chinese (Shen et al, 2004). In addition, patients with cardiac cancer had a significantly higher frequency of the Arg/Arg genotype than chronic gastritis, DU and non-cardiac cancer in the UK (Zhang et al, 2004).…”
Section: Discussionmentioning
confidence: 91%
“…Such changes may contribute to tumor progression and a poor prognosis (Katkoori et al, 2009). Taking into consideration of the extensive role of p53 in GC, hence, to derive a more precise estimation of the association of Arg72Pro polymorphism between p53 gene and GC, we performed a meta-analysis of all eligible case-control studies (Hamajima et al, 2002;Hiyama et al, 2002;Zhang et al, 2003;Shen et al, 2004;Wu et al, 2004;Lai et al, 2005;Mu et al, 2005;Pérez-Pérez et al, 2005;Sul et al, 2006;Yi et al, 2006;Capelláet al, 2008;De Feo et al, 2009;Gomes de Souza et al, 2009;Kim et al, 2010;Mojtahedi et al, 2010;Shirai et al, 2010;Ihsan et al, 2011;Song et al, 2011;Zhu et al, 2012).…”
mentioning
confidence: 99%
“…В литературе описаны ассоциации изучаемого полиморфизма гена ТР53 с разными морфологическими вариантами РЖ. Gao et al показали, что носительство аллеля 72Pro гена ТР53 ассоциировано с повышенным риском формирования диффузного типа РЖ среди азиатов, но пониженным риском развития интестинального типа РЖ среди европеоидов [35], что подтверж-дается метаанализом, проведённым B. Xiang et al [28]. В настоящей работе не обнаружено связи генотипов ТР53 с риском развития диффузного или интестинального типов рака желудка.…”
Section: Discussionunclassified